Burundi : Poverty Reduction Strategy Paper; Second Implementation Report. (IMF Staff Country Reports; Country Report ;, 2010)
The implementation of the Growth and Poverty Reduction Strategy Framework (GPRSF) first describes the characteristics of poverty in Burundi before proceeding to review progress made in terms of each strategic axis. The analysis of macroeconomic performance, including the real sector, inflation, budgetary framework, the real sector [sic], and currency completes this report. In this context of extreme poverty and given the link between population numbers and poverty reduction, it is crucial that issues related to demographic pressure be clearly taken into account in all development programs.